Bioassay vs. immunoassay for quantification of interleukin-6 in biological fluids - Papadopoulos, N. G.; Dedoussis, G. V.; Baxevanis, C. N.; Papamichail, M. (J Clin Lab Anal, 1995)
As several possible prognostic and therapeutic applications of interleukin-6 are currently under trial, the available methods for its quantification in biological fluids should be evaluated. In this report, the 7TD1 hybridoma bioassay is compared to an enzyme immunoassay for the determination of interleukin-6 in serum and plasma of normal subjects and patients with cancer, sepsis, and systemic lupus erythematosus, as well as in malignant pleural effusions and culture supernatants. The results show a good correlation between the two methods in all cases. Mean values of the examined groups were statistically different between the assays only in the case of septic patients. This may be attributed either to the influence of other molecules on the assays or to the nonlinearity of the dose-response curves. Since immunoassays are easier to perform, it seems that they are more suitable for routine use, the bioassay being preferable in cases where increased sensitivity is required.
Keywords: B-Lymphocytes Biological Assay Cell Division Cells; Cultured Culture Media Dose-Response Relationship; Drug Humans Hybridomas Immunoenzyme Techniques Interleukin-6 Leukocytes; Mononuclear Lupus Erythematosus; Systemic Neoplasms Pleural Effusion Regression Analysis Reproducibility of Results Sensitivity and Specificity Sepsis